Health Care Systems Engineering for Scientists and Practitioners HCSE, Lyon, France, May 2015 - Matta, Andrea; Sahin, Evren; Li, Jingshan; Guinet, Alain; Vandaele, Nico J. (Springer Proceedings in Mathematics & Statistics, 2016)
In this volume, scientists and practitioners write about new methods and technologies for improving the operation of health care organizations. Statistical analyses play an important role in these methods with the implications of simulation and modeling applied to the future of health care. Papers are based on work presented at the Second International Conference on Health Care Systems Engineering (HCSE2015) in Lyon, France. The conference was a rare opportunity for scientists and practitioners to share work directly with each other. Each resulting paper received a double blind review. Paper topics include: hospital drug logistics, emergency care, simulation in patient care, and models for home care services. Discusses statistical analysis and operations management for health care delivery systems based on real case studies Papers in this volume received a double blind review Brings together the work of scientists, practitioners, and clinicians to unite research and practice in the future of these systems Topics include: hospital drug logistics, emergency care, modeling and simulation in patient care and healthcare organizations and in home care services.